Comparative analysis between Liquid Based Cytology and Conventional Pap Smears at B P Koirala Memorial Cancer Hospital in Bharatpur, Chitwan, Nepal - Pun, CB; Shrestha, S; Bhatta, RR; Pandey, G; Uprety, S; Bastakoti, S; Bhattarai, I; Zhigang, Miao; Chenpeng, Wu (Nepalese Journal of Cancer, 2018)
Background and Objective: Liquid based cytology was introduced at B P Koirala Memorial Cancer Hospital in Bharatpur, Chitwan, Nepal, on 29th November 2017. The objective of this study was to compare the results of conventional pap smears over six (6) months periods from 29th May 2017 to 28th November 2017 with the results of liquid based cytology smears over six (6) months periods from 29th November 2017 to 28th May 2018. Methods: This is retrospective study. The results of conventional pap smears over 6 months and the results of liquid based cytology smears over 6 months periods were retrieved and analysed to give overall reporting profiles and compared between the two methods. Results: The percentage of unsatisfactory smears fell 3.9% by conventional pap smears methods where as the percentage of unsatisfactory smears fell 1.2% by liquid based cytology smears. There was an increase in the number of smears reported as dyskaryosis of any grade by liquid based cytology methods. Conclusion: The introduction of liquid based cytology led to improvements in unsatisfactory smear rates and also with significant pick up rates of dyskaryosis were maintained and improved.